The chitinase-like protein YKL-40 modulates cystic fibrosis lung disease - Hector, Andreas; Kormann, Michael; Mack, Ines; Latzin, Philipp; Casaulta, Carmen; Kieninger, Elisabeth; Zhou-Suckow, Zhe; Yildirim, Ali Ö; Bohla, Alexander; Rieber, Nikolaus; Kappler, Matthias; Koller, Barbara; et al. (PLOS ONE, 2011)
The chitinase-like protein YKL-40 was found to be increased in patients with severe asthma and chronic obstructive pulmonary disease (COPD), two disease conditions featuring neutrophilic infiltrates. Based on these studies and a previous report indicating that neutrophils secrete YKL-40, we hypothesized that YKL-40 plays a key role in cystic fibrosis (CF) lung disease, a prototypic neutrophilic disease. The aim of this study was (i) to analyze YKL-40 levels in human and murine CF lung disease and (ii) to investigate whether YKL-40 single-nucleotide polymorphisms (SNPs) modulate CF lung disease severity. YKL-40 protein levels were quantified in serum and sputum supernatants from CF patients and control individuals. Levels of the murine homologue BRP-39 were analyzed in airway fluids from CF-like βENaC-Tg mice. YKL-40SNPs were analyzed in CF patients. YKL-40 levels were increased in sputum supernatants and in serum from CF patients compared to healthy control individuals. Within CF patients, YKL-40 levels were higher in sputum than in serum. BRP-39 levels were increased in airways fluids from βENaC-Tg mice compared to wild-type littermates. In both CF patients and βENaC-Tg mice, YKL-40/BRP-39 airway levels correlated with the severity of pulmonary obstruction. Two YKL-40 SNPs (rs871799 and rs880633) were found to modulate age-adjusted lung function in CF patients. YKL-40/BRP-39 levelsare increased in human and murine CF airway fluids, correlate with pulmonary function and modulate CF lung disease severity genetically. These findings suggest YKL-40 as a potential biomarker in CF lung disease.